Active Gate Driver for Improving Current Sharing Performance of Paralleled High-Power SiC MOSFET Modules - Wen, Yang; Yang, Yuan; Gao, Yong (IEEE transactions on power electronics, 2021)
Featuring higher switching speed and lower losses, the silicon carbide MOSFETs (SiC MOSFETs) are widely used in higher power density and higher efficiency power electronic applications as a new solution. Due to the limited current capability of a single module, more modules parallel-connected are necessary for higher power application. However, current sharing is the key obstacle. In this article, an active gate driver (AGD) for high-power SiC MOSFETs is presented to balance the currents of parallel-connected SiC MOSFET modules. The principle of the AGD is based on dynamic gate drive voltage adjustment to synchronize current edges and current slopes among parallel-connected SiC MOSFET modules automatically. Each AGD measures and controls the current of its SiC MOSFET module individually. No extra supervising control circuit is needed. In addition, the hardware and software configurations are independent of the system design and no restrictions on the number of SiC MOSFET modules connected in parallel exist. Finally, the switching performance of the AGD was experimentally verified on two parallel-connected SiC MOSFET modules in a multipulse test under constant and variable load currents. In addition, the effectiveness of AGD under different control topologies has been studied with simulation and verified using three parallel-connected SiC MOSFET modules.